Tailoring hydroxyapatite suspensions by stirred bead milling. Issue 17 (1st September 2022) - Navarrete-Segado, P.; Tourbin, M.; Grossin, D.; Frances, C.
Abstract : The present work deals with the use of stirred bead milling process to tune the hydroxyapatite particles size adjusting the process conditions. Our goal is to find the optimal parameters to obtain particulate suspensions within a 0.2–1.5 μm particle size range. This size range is preferable to produce spherical feedstock for powder bed fusion technologies through the atomization process. A Darvan C dispersant agent dosage of 2.1 mg m −2 (active component) to the specific surface of the ceramic was found, through stability and rheological analyses, to be the most outstanding dosage for stabilizing the dispersion. Milling chamber, bead wear, and energy consumption were evaluated and minimized, finding the most efficient operating parameter setting for the process. For the studied material, the use of a fast stirrer speed, smaller grinding media size, and higher solids concentration increased the energy efficiency. This work confirmed the presented laboratory-scale milling process as a promising method to study the processing of hydroxyapatite-filled slurries, as a first-step product, on the manufacture of hydroxyapatite microspheres for the powder bed fusion industry.